Dampak Game Online terhadap Kesehatan Mental Generasi Z - Muhamad Gofar (Gunung Djati Conference Series, 2023)
This study aims to discuss the impact of online games on the mental health of the generation Z. This study uses a qualitative approach by applying descriptive analytical methods. The results and discussion in this study indicate that the negative effects of online games mostly occur in adolescence. This study concludes that the negative impact of online game addiction occurs in 5 aspects such as health aspects, psychological aspects, academic aspects, social aspects and financial aspects. Therefore, it is necessary to handle how to portion online game play so that someone avoids online game addiction which causes damage to mental health.